Evaluating the iron chelator function of sirtinol in non-small cell lung cancer - Petronek, Michael S.; Bayanbold, Khaliunaa; Amegble, Koffi; Tomanek-Chalkley, Ann M.; Allen, Bryan G.; Spitz, Douglas R.; Bailey, Charvann K. (Frontiers in Oncology, 2023)
Sirtinol is an inhibitor of both SIRT1 and 2; however, it also functions as a tridentate iron chelator by binding Fe3+ with 3:1 stoichiometry. The biological consequences of this function remain unexplored. Consistent with preliminary literature, we show that sirtinol can deplete intracellular labile iron pools in both A549 and H1299 non-small cell lung cancer cells acutely. Interestingly, a temporal adaptive response occurs in A549 cells as sirtinol enhances transferrin receptor stability and represses ferritin heavy chain translation through impaired aconitase activity and apparent IRP1 activation. This effect was not observed in H1299 cells. Holo-transferrin supplementation significantly enhanced colony formation in A549 cells while increasing sirtinol toxicity. This effect was not observed in H1299 cells. Thus, the chelator function of sirtinol is a meaningful drug effect that warrants further consideration.